The political theory of parties - Wolkenstein, Fabio (Politik, 2019)
Political theory has for a long time paid scant attention to the topic of political parties and partisanship. In recent times, however, there has emerged a body of theoretical research that seeks to draw attention to the place of parties and partisanship in a well-functioning polity. This article offers an overview of this research, discussing approaches that focus on partisanship as an associative practice, on the one hand, and approaches that focus on the party as an institution, on the other. The article argues that, while the two approaches no doubt usefully complement each other, concentrating on partisanship at the expense of party risks paying insufficient attention to the institutional structures that ultimately connect partisans to the state and allow them to exercise power. This is problematic insofar as it is especially the party as institution whose virtues are currently called into question. Given this, the article proposes to shift the emphasis in theoretical research from partisanship-centred theories to party-centred theories.